Modulation of Capsaicin-Evoked Visceral Pain and Referred Hyperalgesia by Protease-Activated Receptors 1 and 2 - Naoyuki Kawao; Hisao Ikeda; Tomoko Kitano; Ryotaro Kuroda; Fumiko Sekiguchi; Kazuo Kataoka; Yoshihisa Kamanaka; Atsufumi Kawabata (Elsevier, 2004)
Protease-activated receptors (PARs) 1 and 2 are expressed in capsaicin-sensitive sensory neurons, being anti- and pro-nociceptive, respectively. Given the possible cross talk between PAR-2 and capsaicin receptors, we investigated if PAR-2 activation could facilitate capsaicin-evoked visceral pain and referred hyperalgesia in the mouse and also examined the effect of PAR-1 activation in this model. Intracolonic (i.col.) administration of capsaicin triggered visceral pain-related nociceptive behavior, followed by referred hyperalgesia. The capsaicin-evoked visceral nociception was suppressed by intraperitoneal (i.p.) TFLLR-NH2, a PAR-1-activating peptide, but not FTLLR-NH2, a control peptide, and unaffected by i.col. TFLLR-NH2. SLIGRL-NH2, a PAR-2-activating peptide, but not LRGILS-NH2, a control peptide, administered i.col., facilitated the capsaicin-evoked visceral nociception 6 - 18 h after administration, while i.p. SLIGRL-NH2 had no effect. The capsaicin-evoked referred hyperalgesia was augmented by i.col. SLIGRL-NH2, but not LRGILS-NH2, 6 - 18 h after administration, and unaffected by i.p. SLIGRL-NH2, and i.p. or i.col. TFLLR-NH2. Our data suggest that PAR-1 is antinociceptive in processing of visceral pain, whereas PAR-2 expressed in the colonic luminal surface, upon activation, produces delayed sensitization of capsaicin receptors, resulting in facilitation of visceral pain and referred hyperalgesia. Keywords:: protease-activated receptor, visceral pain, capsaicin, referred hyperalgesia